Skin friction reduction by micro bubbles in pipe flow - Erny Afiza, Alias (2012)
Recently, micro bubbles injection has emerged as a promising drag reduction device in ships due to their significant reduction in frictional drag, cost-effectiveness, environmental-friendly and easy to implement in an existing ship. Frictional drag reduces up to 80% by injecting micro bubbles to the boundary layer. However, the mechanism of drag reduction by micro bubbles is complicated and poorly understood. Therefore, this study is sought to clarify the mechanism of drag reduction by micro bubbles in the most basic flow condition as the mechanism remains unknown. Several controllable factors associated with the efficiency of micro bubbles in drag reduction were investigated to identify the optimum condition for skin friction reduction by micro bubbles. As the results, a higher reduction rate was obtained with larger distribution area of attached micro bubbles at the tube wall in smaller Reynolds number. Moreover, the distribution area and size of micro bubbles at the tube wall increase with time and contributed a great effect in pipe friction loss. Furthermore, void fraction contribute a significant effect in micro bubbles efficiency. Flow, pattern and the bubble's behavior were observed by flow visualization. The ideal bubble size and distribution were evaluated by the measurement of skin friction. Based on the tube's visualization, the wall shear stress in the upper half of the tube decreased as -the bubbles were injected into the boundary layer.